Ptarmigan Field Researchers at La Pérouse Bay, Hudson Bay, Manitoba, Canada - Bazely, Dawn R. (1983)
L to R Dawn Bazely, Sue Stephenson, Jim Davies and ptarmigan research dogs, Tasha (left) and Jenny (right) in field track vehicle. Sue and Jim were Kathy Martin's field assistants. Kathy carried out her doctoral research on willow ptarmigans at La Pérouse Bay.